The role of copper species on Cu/[gamma]-Al2O3 catalysts for NH3-SCO reaction - Liang, C.; Li, Xin Yong; Qu, Z.; Tade, Moses; Liu, Shaomin (Elsevier BV North-Holland, 2012)
UV–vis spectra, XRD, H2-TPR, TEM and ESR were used to characterize a series of Cu/y-Al2O3 catalysts, which were prepared by incipient wetness impregnation using copper nitrate, copper acetate or copper sulfate as precursors, to study the role of Cu species on Cu/y-Al2O3 catalysts for NH3–SCO reaction. It was found that the mixture of CuO phase and CuAl2O4 phase formed on various Cu/y-Al2O3 catalysts, and the Cu species and dispersion had significant influence on the Cu/y-Al2O3 activity. Highly dispersed CuO phase on the support would be related with its high activity for the NH3–SCO reaction.